Pemberdayaan Masyarakat Dalam Pelaksanaan Sunat Perempuan Pada Anak di Kelurahan Ladang Bambu Kecamatan Medan Tuntungan - Violent, Violent; Sopiah, Sopiah (Indonesian Journal Publisher, 2022)
Female circumcision or Female Genital Mutilation (FGM) has no health benefits, in fact if carried out excessively it can cause long-term health problems for women. The aim of this community service is to provide health education to parents who have daughters in a traditionally dangerous culture: female circumcision as an indicator of gender equality from a religious, transcultural and reproductive health perspective in Ladang Bambu Village, Medan Tuntungan District. This Community Service is a qualitative approach with an ethnographic approach. The number of participants was 19 people. The results of the research are that female circumcision is a rule and principle in Islam. Female circumcision is not associated with gender equality, but its implementation is based on the demands of local customs or culture and Islamic religious guidance. From a reproductive health perspective, female circumcision is seen as having no benefits. As a follow-up, it is necessary to establish a Regional Regulation for the City of Medan regarding the implementation of female circumcision and disseminate it to the relevant agencies and the community so that this regulation can be implemented. The conclusion of this community service is that the practice of female circumcision is still carried out by the majority of people in Ladang Bambu Village, Medan Tuntungan District, where its implementation is not linked to gender equality, but is based on local cultural demands and Islamic religious guidance.